Heterologous immunization with BNT162b2 followed by mRNA-1273 in dialysis patients: seroconversion and presence of neutralizing antibodies - Kohmer, Niko; Rabenau, Holger F; Ciesek, Sandra; Krämer, Bernhard; Göttmann, Uwe; Keller, Christine; Rose, Daniela; Blume, Carsten; Thomas, Michael; Lammert, Alexander; Lammert, Anne (Nephrology, dialysis, transplantation, 2022)
The vital renal replacement therapy makes it impossible for dialysis patients to distance themselves socially. This results in a high risk of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection and developing coronavuris disease 2019, with excess mortality due to disease burden and immunosuppression. We determined the efficacy of a 100-µg booster of mRNA-1273 (Moderna, Cambridge, MA, USA) 6 months after two doses of BNT162b2 (BioNTech/Pfizer, Mainz, Germany/New York, USA) in 194 SARS-CoV-2-naïve dialysis patients.Anti-SARS-CoV-2 spike antibodies were measured with the Elecsys Anti-SARS-CoV-2 S assay (Roche Diagnostics, Mannheim, Germany) 4 and 10-12 weeks after two doses of BNT162b2 as well as 4 weeks after the mRNA-1273 booster. The presence of neutralizing antibodies was measured by the SARS-CoV-2 Surrogate Virus Neutralization Test (GenScript Biotech, Piscataway, NJ, USA). Two different cut-offs for positivity were used, one according to the manufacturer's specifications and one correlating with positivity in a plaque reduction neutralization test (PRNT). Receiver operating characteristics analyses were performed to match the anti-SARS-CoV-2 spike antibody cut-offs with the cut-offs in the surrogate neutralization assay accordingly.Any level of immunoreactivity determined by the anti-SARS-CoV-2 spike antibody assay was found in 87.3% (n = 144/165) and 90.6% (n = 164/181) of patients 4 and 10-12 weeks, respectively, after two doses of BNT162b2. This was reduced to 68.5% or 60.6% 4 weeks and 51.7% or 35.4% 10-12 weeks, respectively, when using the ROC cut-offs for neutralizing antibodies in the surrogate neutralization test (manufacturer's cut-off ≥103 U/mL and cut-off correlating with PRNT ≥196 U/mL). Four weeks after the mRNA-1273 booster, the concentration of anti-SARS-CoV-2 spike antibodies increased to 23 119.9 U/mL and to 97.3% for both cut-offs of neutralizing antibodies.Two doses of BNT162b2 followed by one dose of mRNA-1273 within 6 months in patients receiving maintenance dialysis resulted in significant titres of SARS-CoV-2 spike antibodies. While two doses of mRNA vaccine achieved adequate humoral immunity in a minority, the third vaccination boosts the development of virus-neutralizing quantities of SARS-CoV-2 spike antibodies (against wild-type SARS-CoV-2) in almost all patients.
Gesehen am 26.02.2024